In Silico Insight into Potent of Anthocyanin Regulation of FKBP52 to Prevent Alzheimer's Disease. (12th May 2014) - Hung, Tzu-Chieh; Chang, Tung-Ti; Fan, Ming-Jen; Lee, Cheng-Chun; Chen, Calvin Yu-Chian
Abstract : Alzheimer's disease (AD) is caused by the hyperphosphorylation of Tau protein aggregation. FKBP52 (FK506 binding protein 52) has been found to inhibit Tau protein aggregation. This study found six different kinds of anthocyanins that have high binding potential. After analyzing the docking positions, hydrophobic interactions, and hydrogen bond interactions, several amino acids were identified that play important roles in protein and ligand interaction. The proteins' variation is described using eigenvectors and the distance between the amino acids during a molecular dynamics simulation (MD). This study investigates the three loops based around Glu85, Tyr113, and Lys121—all of which are important in inducing FKBP52 activation. By performing a molecular dynamic simulation process between unbound proteins and the protein complex with FK506, it was found that ligand targets that docked onto the FK1 domain will decrease the distance between Glu85/Tyr113 and Glu85/Lys121. The FKBP52 structure variation may induce FKBP52 activation and inhibit Tau protein aggregation. The results indicate that anthocyanins might change the conformation of FKBP52 during binding. In addition, the purple anthocyanins, such as cyanidin-3-glucoside and malvidin-3-glucoside, might be better than FK506 in regulating FKBP52 and treating Alzheimer's disease.